Identification and characterization of copy number variations (CNVs) in dengue patients and its impact with vascular leakage / Zuraihan Zakaria - Zakaria, Zuraihan (Institute of Graduate Studies, UiTM, 2016)
Dengue fever is a mosquito-borne tropical disease caused by dengue virus. When infected by any of the four serotypes of dengue viruses, individuals may be asymptomatic or develop a dengue fever. The latter group can progress into severe form of dengue and the etiology of this is still uncertain. This study aims to elucidate copy number variations (CNVs) of the host genes as the factor causing dengue pathogenesis. Blood samples were collected from hospitalized dengue patients and proceeded to DNA extraction. DNA samples (136) were used for genotyping with Human Genome GeneChip 6.0. CNVs were called using Genotyping Console (GTC) 4.1 and Nexus Copy Number 7.0. Results from both algorithms were merged and stringent CNVs were filtered with three public databases; DGV, HapMap3 and SGVP in search for rare case- specific CNVs. Casespecific underlying genes were used in functional analysis with DAVID and IPA to explicate the dengue related biological processes. Significant genes of interest from both softwares were validated using qPCR. Hundred and thirty-six DNA samples from hospitalized dengue patients in four different hospitals were genotyped. A total number of 50,864 (24,806 gains and 26,059 loss) and 34,257 (31,725 gains and 2,534 loss) CNV events were discovered by GTC and Nexus, respectively. After merging, only 3,052 (2,132 gain and 920 loss) stringent CNVs were left…